2017
DOI: 10.1002/bes2.1281
|View full text |Cite
|
Sign up to set email alerts
|

Predation or Scavenging? Prey Body Condition Influences Decision‐Making in a Facultative Predator, the Wolverine

Abstract: What determines whether a predator scavenges or kills its own prey? Using data on wolverines ( Gulo gulo ) in Scandinavia, we studied variation in diet and feeding strategies along a gradient of environmental productivity, seasonality, density, and body mass of their main prey, semidomestic reindeer ( Rangifer tarandus ). Our results suggest that wolverine feeding strategies are flexible and influenced by seasonally dependent responses to prey body condition in combination with carrion supply. Predation was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…Concerning interference relationships between predators, red fox was expected to suppress arctic fox by interference competition and/or intraguild killing (Elmhagen et al 2017). As a potential top predator, wolverine was predicted to potentially suppress both fox species by intraguild killing (Ehrich et al 2016, Mattisson et al 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning interference relationships between predators, red fox was expected to suppress arctic fox by interference competition and/or intraguild killing (Elmhagen et al 2017). As a potential top predator, wolverine was predicted to potentially suppress both fox species by intraguild killing (Ehrich et al 2016, Mattisson et al 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Lynx Lynx lynx is known to limit red fox abundance in boreal forest (Elmhagen et al 2010), but its distribution generally does not comprise Arctic and sub-Arctic tundra (Anon 2015, Breitenmoser et al 2015). Finally, wolverine are known to kill red fox (Mattisson et al 2016), suggesting wolverine potentially could exert top-down control on red fox and counteract its expansion in the mountain tundra.…”
Section: Introductionmentioning
confidence: 99%
“…Predation was the most common cause of death, but proportions of predation differed among landscapes, indicating land-use changes by humans may alter predator-prey dynamics. Fawns are a temporally limited food resource and lack specialized predators; consequently, their generalist predators may make trade-offs between humancreated food resources (e.g., crops) and fawns (Burroughs et al 2006, Mattisson et al 2016. As such, human activity can create a low-risk-high-forage scenario for prey in landscapes with greater human influence (Rodewald et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the southern portion of their North American range, wolverines appear to be tightly linked to the area defined by the presence of persistent spring snow (Aubry et al 2007, Copeland et al 2010, Inman et al 2013. The underlying ecological requirements that drive this close relationship may include denning requirements Copeland 1998, Copeland et al 2010), a dependence on scavenging large ungulate carcasses effectively preserved within and under the snowpack (Mattisson et al 2016), caching food (Inman et al 2012a), and competitor or predator avoidance (Mattisson et al 2016). Heim et al (2017) suggested that the association of wolverines to persistent spring snow makes them vulnerable to climate changes, and McKelvey et al (2011) predicted a 67% loss of wolverine habitat in the western United States by 2059 due to loss of snowpack.…”
Section: Cumulative Impacts Of Climate Change and Winter Recreationmentioning
confidence: 99%